0485 Experience and Attitudes About Prescription Insomnia Medications: Results from an Online Survey of Individuals with Sleeping Difficulties and Insomnia. (27th May 2020) - Sheehan, D; Zee, P C; Steinberg, K; Ginovker, A; Atkins, N; Moline, M
Abstract: Introduction: This survey explored several topics related to living with insomnia/sleeping difficulties. Reported here are patient experience, attitudes, and perspectives about and understanding of prescription medications for insomnia. Methods: The online survey was conducted by The Harris Poll in the U.S. between February 14 and March 8, 2019. Survey respondents ("patients") were adults age ≥18y who had been diagnosed with insomnia (11% of respondents), or had experienced sleeping difficulties (defined as difficulty falling asleep or staying asleep for ≥3 nights/week for ≥3 months; 89% of respondents). Raw survey data were weighted by relevant factors to be representative of the total U.S. adult population with insomnia/sleeping difficulties. Results: Among 525 patients (mean age 46y; 55% female) who completed the survey, 83 were currently using prescription medication, 45 used prescription medication previously, and 397 had no prescription medication history. The majority of all patients "somewhat" or "strongly" agreed they were "concerned about the safety risks of sleep medications currently available by prescription" (79%); felt "there have got to be better medications that help people sleep" (74%); and that they "wish there were more medications to choose from" (67%). Within the group of respondents with current/past prescription history (n=128), 63%, 23%, and 14% had tried 1-2, 3-4, or ≥5 different prescription medications, respectively. Among reasons for missing/skipping a dose, 20% of respondents with current/past prescription history selected for each response that they "do not feel my medication is effective"; "do not like the way my medication makes me feel when I wake up the next morning"; and "prefer not to take my medication every night unless absolutely necessary." Conclusion: Results from this online survey provide insights into patient attitudes toward pharmacotherapy and indicate that a significant number of insomnia patients feel dissatisfied with medication treatment options, including concerns regarding safety and side effects. Support: Eisai Inc.